2011
DOI: 10.1287/mnsc.1100.1302
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Sequencing and Scheduling in Coil Coating

Abstract: doi 10.1287/mnsc.1100.130

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 24 publications
0
25
0
2
Order By: Relevance
“…In the context of applying 2-Union Independent Set to coil coating-a process in steel manufacturing- Höhn et al (2011) showed NP-hardness of 2-Union Independent Set on the so-called M-composite 2-union graphs (which arise in their application), and showed a dynamic programming based algorithm running in polynomial time for constant M, where the degree of the polynomial depends on M. They additionally provided experimental studies based on heuristics using mathematical programming.…”
Section: Known Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of applying 2-Union Independent Set to coil coating-a process in steel manufacturing- Höhn et al (2011) showed NP-hardness of 2-Union Independent Set on the so-called M-composite 2-union graphs (which arise in their application), and showed a dynamic programming based algorithm running in polynomial time for constant M, where the degree of the polynomial depends on M. They additionally provided experimental studies based on heuristics using mathematical programming.…”
Section: Known Resultsmentioning
confidence: 99%
“…Since 2-Union Independent Set is NP-hard (Bar-Yehuda et al 2006), there is little hope to find optimal solutions within polynomial time. Instead of following the route of approximation algorithms and heuristics (Spieksma 1999;Bar-Yehuda et al 2006;Höhn et al 2011), we aim for solving the problem optimally using fixed-parameter algorithms (Downey and Fellows 2013;Flum and Grohe 2006;Niedermeier 2006), a concept to date largely neglected in the field of scheduling problems (Marx 2011;Mnich and Wiese 2014). 2.…”
Section: -Union Independent Setmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang et al [12] and Ouelhadj et al [13] studied the problem in a dynamic environment where unforeseen changes occur in the production system. Some researchers have also addressed planning and scheduling in downstream production lines such as hot rolling and cold rolling among which [14][15][16][17] can be pointed out. There are significant differences between our problem and theirs, e.g, ladle-, tundish-, and mold-related issues are irrelevant in their problems.…”
Section: Literature Reviewmentioning
confidence: 99%